Pengalaman Seksual Ibu Primipara di Kecamatan Nusa Laut Maluku Tengah - Parinussa, Nenny (Universitas Fort De Kock Bukittinggi, 2020)
Background : Pregnancy brings changes to the physical, psychological and hormonal conditions of every pregnant woman which will affect emotions and sexual behavior. Changes in sexual behavior in pregnant women vary in each trimester of pregnancy. Aim : The purpose of this study was to gain a deep understanding of the sexual experiences of primipara mothers in the nusalaut district. Methode : The design used is qualitative research through a phenomenological approach using semi-structured in-depth interview methods. Participants were five postpartum primipara mothers who were obtained by purposive sampling. Data were collected in the form of recorded interviews and field notes analyzed using the Collaizzi technique. Result : From the results of the study identified four themes, namely: 1) Perceptions about sexual relations during pregnancy; 2) Experience of sexual activity during pregnancy; 3) Factors that influence sexual activity during pregnancy; 4) Social support about sexual activity during pregnancy; 5) The impact of sexual relations on the comfort of the mother during pregnancy; 6) Foreplay that is done before starting sexual relations. Conclusion : It is recommended to provide understanding related to sexual relations during pregnancy.Keywords: Phenomenology Study, Sexual Experience, Primipara Mother